Nailed it! : baking challenges for the rest of us - Maclean, Heather, 1972- (Abrams Image, 2021)
On the show Nailed it!, everyday people bake-- and have a good time doing it. Everyone starts out less-than-perfect, but things don't have to be perfect to be wonderful. This book shares the tips, tricks, detailed recipes, and simplified shortcuts behind the favorite episodes of the show, allowing even inexperienced bakers a fighting chance. Put your skills to the test, and have a blast doing it, whether your creation turns into a mouthwatering masterpiece or a delicious disaster. -- adapted from Introduction and back cover.